Use of oral osmotic hydromorphone in opioid switch for cancer pain - Rosa Palomba; Cristiano Minucci; Marco Graffi; Ilaria Santoriello; Emiliana Matania (Publiediting, 2008)
Hydromorphone is a semi-synthetic opioid and it is a powerful µ receptor agonist. Hydromorphone has a short half-life (approximately 1 hour), but the controlled release formulation Oral Osmotic extends the duration of action and provides constant pain control. The aim of this study was to assess effectiveness and safety of a protocol for the switch from transdermic fentanyl - controlled release morphine - controlled release oxycodone to oral osmotic hydromorphone. Twentyeight patients with uncontrolled cancer pain (VAS≥7), taking high doses of fentanyl, morphine or oxycodone were included in the study. In these patients was administered hydromorphone at doses proportional to previous therapy. The switch produced statistically signifi cant reduction of the VAS values and a reduction of the adverse effects. The identifi cation of the correct dosage of hydromorphone was simple and quick. Our results show that the switch to hydromorphone is safe, simple and effective.